International and comparative competition law - Dabbah, Maher M. (Cambridge University Press, 2010)
This thorough appraisal of competition law and policy from an international and comparative perspective covers the role of different international organisations active in the area, the significance of multinational enterprises and, in particular, the differences between US and EU systems. Taking examples from regions such as Africa, the Middle East and Asia, Maher M. Dabbah looks at the law and policy in developing countries and at a regional level, the internationalisation of competition law and the doctrines of extraterritoriality, bilateral cooperation and multilateral cooperation as well as the relationship between competition and trade policy. The book should prove useful to anyone who is interested in gaining an insight into the international dimension of competition law and policy. It is written in a language and style which make such a complex topic both possible to understand and enjoyable.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Antitrust law.; Conflict of laws -- Antitrust law.; Antitrust law (International law)